The interaction between antecedents and consequences of brand love – can extraversion as a personality trait moderate this interaction - GÜSAN KÖSE, GÖZDE; KELEMCİ, GÜLPINAR (My University, 2022)
Purpose- Today, the most important factor for every brand is to attract consumers to them in a competitive environment and to develop and maintain long-term relationships with them. At this point, businesses are trying to establish a link between their brands. One of the most important ways to create this bond is to build brand love. In this context, the concept of brand love has become extremely important for marketing science. The brands that have become love brands in the eyes of consumers are mentioned by consumers on every platform and provide a competitive advantage for businesses (McDowell, 2011). Thus, consumer-brand relationships have become a popular topic in marketing literature, which has attracted the attention of marketing researchers as well as academics (Albert & Merunka, 2013; Carroll & Ahuvia, 2006; Nawaz, Jiang, Alam, & Nawaz, 2020). Brand love is affected by many factors, which are called antecedents. This study focuses on examining the relationship between the antecedents and consequences of brand love. In today’s digital world, social media platforms have become an indispensable practice in life. We consider Instagram as a brand, and it exhibits brand love. The first purpose of this study is to reveal the relationship between the antecedents and consequences of brand love in the context of Instagram. The main factors, which are analyzed within the scope of the study, are the perceived hedonic value of Instagram, the utilitarian influence of reference groups as well as consumer-oriented perceived brand equity as the antecedents of brand love. We take brand loyalty as a consequence of brand love, which is listed as one of the outcomes of brand love from the consumer perspective. The second aim of this study is to investigate the mediator role of extraversion on brand love and brand loyalty, which is one of the five broad personality traits. Methodology- Within the scope of these purposes, data were collected by an online survey method from 287 people using Instagram with the help of snowball sampling. The collected data was analyzed with SPSS 16 and AMOS 25 package programs. Exploratory factor analysis and confirmatory factor analysis were used to determine the validity of the scales. Then the research hypotheses tested using structural equation modeling. Findings- The analysis reveals that the hedonic value of using Instagram, the utilitarian influence of reference groups, and brand equity have a positive effect on brand love, while brand love has a positive effect on brand loyalty. Furthermore, it is revealed that extraversion has a partial mediating effect on the relationship between brand love and brand loyalty. Conclusion-In this regard, this study reveals the importance and benefits of brand love and the proposed antecedents and consequences of brand love, as well as extraversion for social media and other sectors of industry. By understanding the antecedents and consequences of brand love, managers can get a better understanding of the factors that orientate consumers’ inner feelings for the brand. As a result of this study, brand love and other variables which were part of the model are highly important factors which influence the connectivity between consumers and brands. If the love for the brand is higher, the loyalty for the brand from the perspective of consumers is also higher because brand love has a positive effect on brand loyalty. Therefore, it is extremely important for businesses to try to establish a link between their consumers and the brand and to ensure the formation of brand love. By establishing a a mutual relation between a consumer and a brand, businesses can likewise ensure the loyalty of the consumer towards the brand. Extroverts are more likely to be in a more direct contact with the brand because of their feelings toward it than introverts. Since hedonic value of product also has a positive effect on brand love and loyalty likewise, businesses can use this situation for their own profit by introducing various and different products that will attract customers of this character.
Keywords: Brand love; hedonic value; influence of reference groups; extraversion; brand equity